Drug abuse proportion and pattern in Bangladesh: a laboratory based study (Bangladesh Journal of Psychiatry, 2021)
Drug addiction is now a great concern for Bangladesh because of its geographical location. It appears as a growing challenge for this developing country. The aim of the study was to find out the proportion and pattern of drug abuse among the adults. This lab based cross sectional study was carried out on 4115 individuals at Armed Forces Institute of Pathology (AFIP) from July 2019 to June 2020 on both males and females, reporting for screening of drug abuse for employment, admission in educational institutes and suspects in working places. After justification of urine specimen by urinary creatinine level, qualitative screening test for 12 drugs of abuse was carried out by ‘Abon’ multi-drug one step multi-line screen test device. Screen positive samples were then confirmed with homogeneous enzyme immunoassay in Architect c 8000 analyzer of Abbott. The results showed that, 221 (5.37%) were positive for abuse of one or multiple drugs. Mostly the younger age group mean±SD, 24.69±6.52 years (IQR: 20-28 years) were the drug abusers. The most abused drugs was benzodiazepines (36.6%) next in order were marijuana or tetra-hydro cannabinoids (35.8%), amphetamine and methamphetamine (19.8%), opiates (4.7%) and methylene di-oxy methamphetamine (MDMA) or ecstasy (3.1%). The most of the abusers’ used a single drug (85%). Marijuana or tetra-hydro cannabinoids was the commonest drug in use in case of multiple drug usage of different combinations. This study showed the pattern of abused drugs and highlighted that, the younger age groups were the most liable group. So, they need more attention from their parents, society and educational institutes to overcome the worrying situation. Bang J Psychiatry 2021;35(1): 5-9